أثر تطبيق الضرائب المؤجلة على جودة القوائم المالية وفق النظام المحاسبي المالي - بن شهيدة, أسماء (My University, 2019)
This study aims to demonstrate the extent of the impact of the deferred taxes application on the financial statements that, in order to analyze the extent of differences in the deferred taxes treatment according to international accounting standards , as well as the Mostaganem port Algerian financial accounting system, the practical study through thecompany. The study concluded that the effect of deferred taxes on the financial statements, through the impact on the financial result of the entreprise but we found also there is still a disparity between international accounting standards and Algerian financial accounting system in deferred tax treatment.
مؤسسة ميناء مستغانم
Keywords: ضرائب مؤجلة ، معيار محاسبي رقم 12 ، نظام محاسبي مالي